Successful implementation of diabetes audits in Australia: the Australian National Diabetes Information Audit and Benchmarking (ANDIAB) initiative. Issue 7 (2nd May 2018) - Lee, A. S.; Colagiuri, S.; Flack, J. R.
Abstract: Aim: We developed and implemented a national audit and benchmarking programme to describe the clinical status of people with diabetes attending specialist diabetes services in Australia. Methods: The Australian National Diabetes Information Audit and Benchmarking (ANDIAB) initiative was established as a quality audit activity. De‐identified data on demographic, clinical, biochemical and outcome items were collected from specialist diabetes services across Australia to provide cross‐sectional data on people with diabetes attending specialist centres at least biennially during the years 1998 to 2011. Results: In total, 38 155 sets of data were collected over the eight ANDIAB audits. Each ANDIAB audit achieved its primary objective to collect, collate, analyse, audit and report clinical diabetes data in Australia. Each audit resulted in the production of a pooled data report, as well as individual site reports allowing comparison and benchmarking against other participating sites. Conclusions: The ANDIAB initiative resulted in the largest cross‐sectional national de‐identified dataset describing the clinical status of people with diabetes attending specialist diabetes services in Australia. ANDIAB showed that people treated by specialist services had a high burden of diabetes complications. This quality audit activity provided a framework to guide planning of healthcare services. What's new?: The Australian National Diabetes Information Audit and Benchmarking (ANDIAB) initiative collected comprehensive health data from Australian diabetes specialist services. Individual participating sites could compare and benchmark their practice findings. A large national de‐identified dataset describing diabetes care status was developed. Findings from ANDIAB highlight the high burden of diabetes complications among these individuals and can be used to help plan improvements in diabetes healthcare services.